Expressão gênica de células do cumulus e oócitos bovinos sbmetidos à maturação un vitro com diferentes macromoléculas, EGF e Butirolactina I - Souza, Diego Gouvêa de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to quantify the abundance of genes associated with the development of oocyte competence in oocytes (GDF-9, BMP15 and OOSP1) and in cumulus cells (GREM1, PTGS2, PFKP, AREG, EREG, HAS2, VCAN, PTX3, ADAM10 and ADAM-17) of immature oocytes (GV), in vivo matured (IVMO) and cultured in IVM medium with different macromolecules (FCS, BSA or PVA), different EGF concentrations or pre-cultured with butyrolactone I (BLI) before IVM. The experimental design consisted of three IVM experiments of bovine oocytes, namely: experiment 1, cumulus-oocyte complex matured in culture medium containing 10% FCS or 1 mg/mL PVA or 4 mg/mL BSA; Experiment 2, cumulus-oocyte complex matured in culture medium containing EGF (at concentrations of 0, 10 and 100 ng/mL); and Experiment 3, cumulus-oocyte complex in vitro matured in the absence (BL0) or presence of pre-maturation with 10 μM de BLI (BL12, 12 hours of pre-maturation and 12 hours of IVM, BL24, 24 hours of pre-maturation and 24 hours of IVM). The relative amount of transcripts for GREM1, PTGS2, PFKP and AREG gene was larger than (P <0.05) in cumulus cells of IVMO oocytes in experiments 1 and 2 and for GREM1 gene in experiment 3. In experiment 1, the FCS group exhibited higher (P <0.05) abundance of transcripts of GREM1 and AREG among MIV groups. In experiment 2, the addition of 10 ng/ml to the IVM medium provided an upregulation of EREG. In experiment 3, BL12 showed higher (P <0.05) abundance of AREG and BL24 of EREG and PTX3. Among IVM groups, the GREM1 gene was expressed in larger quantities (P <0.05) in BL12. There was no statistical difference in experiments 1, 2 and 3 among groups of oocytes IVM, IVMO and GV for GDF9, BMP15 and OOSP1 genes. It was concluded that the use of different macromolecules, different EGF concentrations and the performance of pre-culture with BLI change the transcription in the cumulus cell of genes associated with oocyte competence

O objetivo deste estudo foi quantificar a abundância de genes associados com a competência de desenvolvimento em oócitos (GDF-9, BMP15 e OOSP1) e nas células do cumulus (GREM1, PTGS2, PFKP, AREG, EREG, HAS2, VCAN, PTX3, ADAM10 e ADAM17), a partir de oócitos imaturos (VG), maturados in vivo (MIVO) e cultivados em meio de MIV com diferentes macromoléculas (SFB, BSA ou PVA), diferentes concentrações de EGF ou pré-cultivados com butirolactona I (BLI) antes da MIV. O delineamento experimental consistiu de três experimentos de MIV de oócitos bovinos, a saber: experimento 1, complexos cumulus-oócito maturados em meio de cultivo contendo 10% de SFB ou 1 mg/mL de PVA ou 4 mg/mL de BSA; experimento 2, complexos cumulus-oócito maturados em meio de cultivo contendo EGF (nas concentrações de 0, 10 e 100 ng/mL); e experimento 3, complexos cumulus-oócito maturados in vitro na ausência (BL0) ou presença de pré-maturação com 10 μM de BLI ( BL12, 12 horas de pré-maturação e 12 horas de MIV; BL24, 24 horas de prématuração e 24 horas de MIV). A quantidade relativa de transcritos para o gene GREM1, PTGS2, PFKP e AREG foi maior do que (P<0,05) nas células do cumulus de oócitos MIVO, nos experimentos 1 e 2 e para o gene GREM1 no experimento 3. No experimento 1, o grupo SFB exibiu maior (P<0,05) abundância de transcritos de GREM1 e AREG entre os grupos MIV. No experimento 2, a adição de 10 ng/mL ao meio de MIV propiciou uma regulação positiva de EREG. No experimento 3, BL12 apresentou maior (P<0,05) abundância de AREG e o BL24 de EREG e PTX3. Entre os grupos de MIV, o gene GREM1 foi expresso em maior quantidade (P<0,05) no BL12. Não houve diferença estatística nos experimentos 1, 2 e 3 entre os grupos de oócitos MIV, MIVO e VG para os genes GDF9, BMP15 e OOSP1. Conclui-se que, a utilização de diferentes macromoléculas, diferentes concentrações de EGF e a realização de précultivo com BLI altera a transcrição nas células ...
Gene expression if cumulus cell and bovine oocytes submitted to in vitro maturation with different macromolecules, EGF and butyrolactone I
Keywords: Biotecnologia animal; Expressão gênica; Oócitos; Técnicas de maturação in vitro de oócitos; In Vitro Oocyte Maturation Techniques